A Descriptive Study of Mental Health and Physical Activity in Adolescents - Desak Made Ari Dwi Jayanti; Gusti Ayu Putu Satya Laksmi; I Nyoman Dharma Wisnawa; I Gede Satria Astawa (Babali Nursing Research, 2023)
Introduction: Mental health is a condition in which individuals realize their potential, are able to contribute, prosper, work productively, and can contribute to the environment. Physical activity is any body movement capable of producing energy. The purpose of this study was to figure out the description of mental health and physical activity in adolescents. Methods: The study used a quantitative descriptive research method with a cross-sectional approach. The population was 780 youths, and a sample of 265 people was calculated using the Slovin formula. The sampling method used stratified random sampling. The measuring tool for mental health variables used the SRQ-29 and physical activity used the IPAQ.Results: The results of the study showed that 46.4% of the respondents had symptoms of mental-emotional disorders, none of the respondents used psychoactive substances, 4.9% of the respondents had psychotic symptoms/psychosis, and 7.5% of the respondents had symptoms of PTSD. In the physical activity variable, the majority of the respondents had moderate physical activity, 39.6%.Conclusion: The mental health problems experienced by the respondents and the physical activity undertaken can be influenced by characteristics such as age, sex, relationships with colleagues, stress, and bullying. Respondents are expected to pay attention to their mental health conditions and continue to perform physical activities in their daily lives.